Accumulating Cares: Women, Whiteness, and the Affective Labour of Responsible Reproduction in Neoliberal Times - Watson, Amanda (Université d'Ottawa / University of Ottawa, 2016)
This thesis examines contemporary popular and news media representation of motherhood and labour in Canada and the United States. I explore what texts about motherhood and maternal labour suggest about gendered responsibilities to citizenship in neoliberal conditions. Building on important feminist research in the fields of citizenship, care, and the welfare state, I ask how are mothers being socially responsibilized toward multiple forms of labour simultaneously and to what effect? By engaging feminist theories of citizenship and bridging this field with feminist theories of science, media, and affect, I demonstrate how, under neoliberal conditions and in precarious circumstances, the ways in which women appear to juggle their commitments to paid and unpaid labour, determines how mainstream discourses reflect their value as citizens. This dissertation uses feminist critical discourse analysis to assess how, as women are responsibilized toward unpaid intimate work in newly empirical ways at the same time that they are encouraged to pursue career success in full-time paid employment, contemporary women in Canada and the United States are encouraged to rise above welfare retrenchment and inadequate provision by juggling “it all.” My thesis is an intersectional feminist project that interrogates questions of gendered citizenship and maternal affect, and I join feminist political theorists in applying pressure to the field of citizenship studies to centre reproduction in discussion of gendered welfare.
Keywords: care work; labour; reproduction; citizenship; responsibility; motherhood; gender; whiteness; feminist political theory; affect; representation